Peruvian Agro-Export Sector: a Competitiveness Study on Their Main Products in the Period 2010-2019 - Escalante Yaulilahua, Danton Arturo (2023)
Peruvian agricultural export products have gained importance in world markets in recent years. Therefore, the main objective of the study was to compare the level of competitiveness of the five main Peruvian products against similar products from other Latin American countries in a pre-pandemic and energy crisis development period (2010-2019). For this, two categories were analyzed: the level of specialization and the level of competitiveness with the competitiveness matrix modified by Lacayo and Morales in 2007. The study found a high level of specialization in all the Peruvian products analyzed, especially for the Blueberry category; likewise, the Grape, the Blueberry and the Avocado presented high levels of competitiveness; while Coffee and Asparagus were the least competitive due to their low performance in the analysis of the level of specialization.